A new species of long-tailed mouse, genus Oligoryzomys Bangs, 1900 (Rodentia: Cricetidae), from the Bolivian Yungas - Hurtado, Natalí; D’elía, Guillermo (Zootaxa, 2018)
Andean long-tailed mice of the genus Oligoryzomys have a complex and instable taxonomic history. Recent studies, in addition to circumscribe O. destructor to populations from southern Peru up to the north, and O. brendae to those from Argentina and southern Bolivia, have identified a candidate species in northern Bolivia. Herein, we assessed the status of the mentioned candidate species by morphologically comparing it with O. brendae, its sister group; with O. destructor, which is morphologically similar and distributed parapatrically; and with O. flavescens occidentalis, which is geographically codistributed. Additionally, we compared it with Oryzomys chaparensis, a poorly known form, currently placed in the synonymy of O. microtis, whose type locality is near the known distribution of the Bolivian candidate species. Results show that the assessed form is morphologically diagnosable. This fact together with its phylogenetic distinction allows us to hypothesize that it represents a new species that is named and described here.